The Double Edge Sword of Testosterone’s Role in the COVID-19 Pandemic - Younis, Johnny S.; Skorecki, Karl; Abassi, Zaid (Frontiers in Endocrinology, 2021)
COVID-19 presents an amply complex disease and multifaceted set of disturbances involving several mechanisms of health and disease in the human body. Sex hormones, estrogen and testosterone, seem to play a major role in its pathogenesis, development, spread, severity, and mortality toll. Examination of factors such as age, gender, ethnic background, genetic prevalence and existing co-morbidities, may disclose mechanisms underlying SARS-CoV-2 infection, morbidity, and mortality, paving the way for COVID-19 amelioration and substantial flattening of the infectivity curve. In this mini-review, we focus on the role of testosterone through the intricate mechanisms of disease development and deterioration. Accumulate evidence suggest linkage between high level (normal male level) as well as low level (age-related hypogonadism) of testosterone to disease progression and expansion, supporting its role as a double-edged sword. Unresolved questions point to the essential need for further targeted studies to substantiate these contrasting mechanisms.